The ultimate book of martial arts - Goodman, Fay. (New York, N.Y. : Lorenz Books, 1998)
The history and philosophy, clothing and equipment, etiquette, exercise, and techniques of ten disciplines of martial arts.
Introduction -- Tae kwondo -- Karate -- Aikido -- Ju-jitsu -- Judo -- Kung fu -- Tai chi chuan -- Kendo -- Iaido -- Shinto ryu.
Includes index.
Keywords: Martial arts; Self-defense.; Hand-to-hand fighting, Oriental